Constructing accurate interaction potentials to describe the microsolvation of protonated methane by helium atoms. Issue 12 (10th March 2017) - Kuchenbecker, Dennis; Uhl, Felix; Forbert, Harald; Jansen, Georg; Marx, Dominik
Abstract : An ab initio -derived interaction potential is derived and used in path integral Monte Carlo simulations to investigate stationary-point structures of CH5 + microsolvated by up to four helium atoms. Abstract : Protonated methane, CH5 +, is not only subject to quasi-rigid vibrational motion which describes its unprotonated parent, CH4, but is dominated by large-amplitude motion even in its quantum ground state. This fluxional behavior leads to hydrogen scrambling which sensitively depends on the underlying flat potential energy surface. Yet, it is largely unknown how fluxional species, such as CH5 +, respond to perturbations arising from microsolvation by weakly interacting species, such as those commonly used as tags in messenger-based vibrational action spectroscopies. Here, we construct an intermolecular interaction potential of extrapolated coupled cluster accuracy in order to investigate the microsolvation shell structure of small CH5 + ·He n complexes. Having explicitly demonstrated that three-body contributions are essentially negligible, our analytical CH5 + ⋯He model potential is kept as simple as possible in order to allow for efficient use in the framework of finite-temperature path integral simulations. It is a strictly pairwise additive site–site potential without explicit angular dependence, but critically involves additional pseudo-sites in addition to the usual atom-based interaction sites. The parameterized potential is shown to accurately describe the microsolvation of all low-lying stationary points on the potential energy surface, namely the e- C s, s- C s, C 2v, and C 4v structures. Based on path integral Monte Carlo simulations at ultralow temperature, about 1 K, we disclose that the many-body helium density in three-dimensional space, and thus the microsolvation pattern, depends sensitively on the combination of the solute structure and the number of attached He atoms.